Immigration Law Regulations Against Traditional Border Crossers in the Border Area of Merauke Regency - Samingun Samingun; Julianto Jover Jotam Kalalo (Faculty of Law, Musamus University, 2020)
The state of Indonesia is a state of law, everything is regulated by law. The Indonesian territory from Sabang to Merauke has borders with other foreign countries. The West is bordered by other countries even though it is separated from the sea, in the north it is directly adjacent to the mainland area with Malaysia, in the south it borders on land with Timor Leste and in the eastern part it is directly adjacent to Papua New Guinea. The entire area bordering either directly or indirectly is regulated by immigration law. Immigration law regulations have been well regulated, starting from the highest regulations to the lowest regulations in their respective regions. In this case, in the border area of ​​Merauke district, which is directly adjacent to Papua New Guinea, there are immigration law regulations that are used based on positive Indonesian law, in this case laws and there are also customary laws from the local community. The occurrence of legal pluralism in the land border area of ​​Merauke district is due to the existence of customary law that is still thick in the lives of the people in this border area, resulting in an immigration law regulation that must conform to the policies of local indigenous peoples who always cross borders from Indonesia to Papua New Guinea or vice versa, known as the designation of traditional border crossers.